Mathematics Teachers in Teaching 4C Skills: School-University Perspective - Pikir Wisnu Wijayanto; Jitu Halomoan Lumbantoruan; Loso Judijanto; Budi Mardikawati; Nuril Huda (Journal of Education Reseach and Evaluation, 2024)
In the 21st century, teacher education is required to look for new ways to improve the quality of mathematics teachers. However, the facts seen from the PISA test show that the achievement of Indonesian students is always low. Additionally, the OECD reports that only 1% of students in Indonesia are able to answer questions at a low level. The research aims to identify and find out what teacher educators face in preparing mathematics teachers with 4C skills and knowing solutions to 4C difficulties. The research method is a qualitative exploratory case study with a single case study design. The subjects were teachers at schools and prospective teachers at universities. Data collection techniques using documents and interviews. Ten prospective teachers from a university perspective and ten in-service teachers from a school perspective. The data analysis technique uses the constant comparative analysis method. The research results found five common challenges: lack of learning ability and motivation among prospective teachers, pedagogical challenges, lack of capacity and conceptual understanding of 4C skills among teacher educators, lack of supporting programs and facilities, and political challenges. Another finding is that teacher capacity is the two main concerns; universities must implement new, dynamic learning systems to equip mathematics teacher graduates with resources that teach 4C skills innovatively.